ETIKA PROFESI INSINYUR SEBAGAI PILAR GOOD GOVERNANCE DALAM PELAYANAN PUBLIK - Srisusanti Haris Ladanu; La Ode Muhammad Ichwan Sjachrawy; Hasmawati; Dwi Bayu Putra Pamungkas; Hado; Maudhy Satyadharma (Yayasan Pendidikan Literasi Borneo, 2025)
The quality of public services is a key indicator of the success of good governance. In national development, the engineering profession plays a strategic role due to its involvement in the planning, construction, operation, and supervision of infrastructure and technology-based public services. However, various public service issues such as low infrastructure quality, weak technical accountability, budget inefficiency, and cases of technical failure indicate that aspects of professional ethics have not been fully internalized in engineering practices in the public sector. This article aims to analyze the role of engineering professional ethics as a pillar of good governance in public services by emphasizing the implementation of the Indonesian Engineers Association (PII) Code of Ethics and the value of integrity. This research uses a qualitative approach through literature study with normative-analytical analysis of literature, regulations, and professional documents. The results of the study indicate that engineering professional ethics based on integrity, public responsibility, and professionalism contribute significantly to strengthening the principles of accountability, transparency, effectiveness, and fairness in public services. Therefore, strengthening engineering professional ethics needs to be positioned as an integral part of bureaucratic reform and public service governance in Indonesia.